Form diversity of Japanese barberry (Berberis thunbergii DC.) in the collection and expositions of Kherson state university - N.I. Sushynska (Інтродукція Рослин, 2019)
Objective — to evaluate the viability and decorativeness of introduced forms and hybrids of Berberis thunbergii DC. in collections and expositions of Kherson State University.